Corpus et étude des collocations verbales - Dechamps, Christina (2018)
This research has been financed by Portuguese National Funding through the FCT Fundação para a Ciência e Tecnologia as part of the project of the Centro de Linguística da Universidade Nova de Lisboa – UID/LIN/03213/2013.